The effect of traumatic brain injury on bone healing: an experimental study in a novel in vivo animal model. Issue 4 (April 2015) - Tsitsilonis, Serafeim; Seemann, Ricarda; Misch, Martin; Wichlas, Florian; Haas, Norbert P.; Schmidt-Bleek, Katharina; Kleber, Christian; Schaser, Klaus-Dieter
Abstract: Introduction: Among many factors determining the outcome of complex fractures in polytrauma patients, the role of traumatic brain injury (TBI) remains only partly understood. The aim of the present study was to examine the effect of traumatic brain injury on bone healing through the establishment of a novel standardised animal model that sequentially combines traumatic brain injury (TBI) with a long bone injury. Materials and methods: Thirty-six female twelve-week old C57/BL6 mice were randomised in two groups (fracture (Fx)-group and combined-trauma (Fx/TBI) group). The methods of the Control Cortical Impact Injury for induction of TBI and of the femoral osteotomy, fixed with an external fixator for the simulation of the long bone fracture, were combined. No TBI was induced in the Fx-group. Bone healing was examined using in vivo micro-CT measurements over a period of three weeks. Results: The severity of the TBI was sufficient to stimulate a significantly increased callus formation in the Fx/TBI-group with an acceptable mortality rate. The micro-CT analysis of fracture healing displayed a significantly increased callus volume in the Fx/TBI-group already from the second postoperative week. This difference remained significant throughout the entire study period. Discussion: The successful and standardised combination of TBI and fracture in a mouse model allows systematic and quantitative in vivo analysis of underlying pathways that trigger the mutual interaction between musculoskeletal trauma and brain injury, as well as, corresponding differences in fracture healing using micro-CT methods. Conclusion: The present study offers three new aspects: a standardised model for combined injury of TBI and femoral osteotomy; direct and serial in vivo imaging and quantification of fracture healing response using micro-CT; testing of potentially beneficial therapeutic regimens for fracture treatment in presence of TBI. Thus this model provides a valuable basic approach for the study of the amplifying effect of TBI on callus formation seen in patients with craniocerebral injury and concomitant skeletal trauma.